Intravenous carbamazepine as short‐term replacement therapy for oral carbamazepine in adults with epilepsy: Pooled tolerability results from two open‐label trials. (25th April 2015) - Lee, Deborah; Kalu, Uwa; Halford, Jonathan J.; Biton, Victor; Cloyd, James; Klein, Pavel; Bekersky, Ihor; Peng, Guangbin; Dheerendra, Suresh; Tolbert, Dwain
Summary Objective To report tolerability findings and maintenance of seizure control from a pooled analysis of phase I open‐label trial OV‐1015 (NCT01079351) and phase III study 13181A (NCT01128959). Methods Patients receiving a stable oral dosage of carbamazepine were switched to an intravenous (IV) carbamazepine formulation solubilized in a cyclodextrin matrix (at a 70% dosage conversion) for either a 15‐ or a 30‐min infusion every 6 h for up to 7 days and then switched back. A subset of patients who tolerated 15‐min infusions also received 2‐ to 5‐min (rapid) infusions. Assessments included physical and laboratory evaluations, electrocardiography (ECG) studies, as well as adverse event (AE) monitoring for tolerability. Convulsion/seizure AE terms and data from seizure diaries were used as proxies for the assessment of consistency of seizure control between formulations. Results Of the 203 patients exposed to IV carbamazepine (30 min, n = 43; 15 min, n = 160), 113 received 149 rapid infusions. During infusion, the most commonly reported AEs (≥5%) were dizziness (19%), somnolence (6%), headache (6%), and blurred vision (5%). IV carbamazepine was not associated with clinically relevant cardiac AEs. The tolerability profile appeared similar between patients who received <1, 600 mg/day (n = 174) and ≥1, 600 mg/day (n = 29) carbamazepine. Cyclodextrin exposure was not associated with clinically relevant changes in AEs or renal biomarkers. Seizure control was maintained as patients transitioned between oral and IV carbamazepine. Significance IV carbamazepine administered as multiple 30‐ or 15‐min infusions every 6 h, and as a single rapid infusion, was well tolerated as a short‐term replacement in adults with epilepsy receiving stable dosages of oral carbamazepine. Infusion site reactions, which were generally mild, were the only unique AEs identified; seizure control was generally unchanged when patients were switching between formulations.